Bioethanol and biomethane production from watermelon waste: A circular economy strategy. (March 2023) - Scapini, Thamarys; Bonatto, Charline; Dalastra, Caroline; Bazoti, Suzana Fátima; Camargo, Aline Frumi; Alves Júnior, Sérgio Luiz; Venturin, Bruno; Steinmetz, Ricardo Luis Radis; Kunz, Airton; Fongaro, Gislaine; Treichel, Helen
Abstract: In the present study, bioethanol and biogas were produced from watermelon waste aiming at the integral use of residual biomass in a circular economy context. Watermelon pulp was processed and used as the culture medium for ethanol production with the yeast Wickerhamomyces sp. UFFS-CE-3.1.2 and watermelon rinds were used for biochemical biogas production (BBP) assays. For the ethanol production step from watermelon pulp, the results demonstrate that there was no requirement to supplement the medium with nitrogen sources to achieve satisfactory yields and cell viability. With this, a sequential batch configuration with cell recycling was conducted for thirty cycles, with fermentation yields of around 90% during all recycling, high cell density and viability, and reduced fermentation time from 9 h to 3 h. The results of the biogas production step from watermelon rinds indicate that the biomass performed well, with biogas and methane production of 581 ± 11 mLN ·gVS and 290.63 ± 5.63 mLCH4 ·gVS, respectively, and energetic potential of 15, 461.54 kJ·kgbiomass −1 . Our data provide a perspective on using watermelon waste for biofuel production to reduce the environmental impacts of this biomass disposal, thus contributing to the circular economy and the advances in the field of renewable energy. Graphical abstract: Image 1 Highlights: Proposal for integration of bioenergy recovery from watermelon waste. The use of a non-conventional yeast for high-yield ethanol production (up to 90%). Sequential batch setup in alcoholic fermentation with high yield and cell viability. Watermelon rinds are a substrate of anaerobic digestion with high performance. The use of watermelon waste promotes a circular economy.